2020
DOI: 10.1089/aid.2020.0088
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Interpretation: The Unmet Need for Linguistically and Culturally Competent Care for Latinx People Living with HIV in a Southern Region with a Low Density of Spanish Speakers

Abstract: Latinx people living with HIV (PLWH) experience disparities in health outcomes and face unique barriers to care related to language, intersectional stigma, and immigration status. We aimed to explore the lived experience of Spanish-speaking Latinx PLWH in the nonurban South to better understand how to improve care for this minority language population. We conducted semistructured interviews with 22 participants (10 men, 10 women, 2 transgender women) who were recruited from a Ryan White HIV/AIDS program (RWHAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“… 23 Peer support has been shown to contribute to improved psychosocial and emotional health and wellness, and was maintained in the platform rebuild, as other cohorts demonstrated appreciation for this feature after using it. 30 …”
Section: Resultsmentioning
confidence: 99%
“… 23 Peer support has been shown to contribute to improved psychosocial and emotional health and wellness, and was maintained in the platform rebuild, as other cohorts demonstrated appreciation for this feature after using it. 30 …”
Section: Resultsmentioning
confidence: 99%
“…This is also seen in race/ethnicity breakdowns of viral suppression [33]. Several strategies can be employed to improve viral suppression and CD4 þ cell count in people of color, including addressing the impact of social determinants of health, including racism, discrimination, and poverty, on HIV testing, care, treatment, and support services [31], providing culturally competent care to patients from diverse backgrounds [34], and using data to direct interventions designed to improve viral suppression to communities with low viral suppression [17].…”
Section: Discussionmentioning
confidence: 99%
“…For these populations, our clinic has an opportunity to improve our communication about safer sex practices. A mixed methods study in 2020 based in our clinic found that Spanish-speaking PWH with limited English language were dissatisfied with their care due to language and cultural barriers between patients and clinicians [ 26 ]. Therefore, language barriers accompanied by inadequate interpreter services may play a role in our clinicians’ communication and discussions about safer sex practices with Hispanic men with HIV.…”
Section: Discussionmentioning
confidence: 99%